A Trust‐Based Pact in Research Biobanks. From Theory to Practice. (26th August 2015) - Sanchini, Virginia; Bonizzi, Giuseppina; Disalvatore, Davide; Monturano, Massimo; Pece, Salvatore; Viale, Giuseppe; Di Fiore, Pier Paolo; Boniolo, Giovanni
Abstract: Traditional Informed Consent is becoming increasingly inadequate, especially in the context of research biobanks. How much information is needed by patients for their consent to be truly informed? How does the quality of the information they receive match up to the quality of the information they ought to receive? How can information be conveyed fairly about future, non‐predictable lines of research? To circumvent these difficulties, some scholars have proposed that current consent guidelines should be reassessed, with trust being used as a guiding principle instead of information. Here, we analyse one of these proposals, based on a Participation Pact, which is already being offered to patients at the Istituto Europeo di Oncologia, a comprehensive cancer hospital in Milan, Italy.